1996
DOI: 10.1063/1.1147104
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative detection of low energy positive and negative ions with a channel electron multiplier

Abstract: We have constructed ion optics which, when interfaced with a channel electron multiplier ͑CEM͒, make possible quantitative measurements of positive and negative ion fluxes. We describe the design and operation of a detection system using these optics and present a calibration of the CEM for low energy ͑0.2-8.7 keV͒ positive and negative oxygen ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…The present measurements also agree favorably with absolute detection efficiencies measured for O Ϫ and O ϩ incident on two distinct channel electron multipliers by Keller and Cooper. 9 These results and the present ones indicate that D Ϫ ϾD ϩ for EϽ7500 eV. Carefully designed electrostatic shielding in the experiment by Keller and Cooper 9 ensured the exclusion of stray secondary electrons from enhancing the measured O Ϫ detection efficiency; it was thus concluded that the difference might be due to different secondary electron coefficients for O ϩ and O Ϫ impacting a CEM surface.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…The present measurements also agree favorably with absolute detection efficiencies measured for O Ϫ and O ϩ incident on two distinct channel electron multipliers by Keller and Cooper. 9 These results and the present ones indicate that D Ϫ ϾD ϩ for EϽ7500 eV. Carefully designed electrostatic shielding in the experiment by Keller and Cooper 9 ensured the exclusion of stray secondary electrons from enhancing the measured O Ϫ detection efficiency; it was thus concluded that the difference might be due to different secondary electron coefficients for O ϩ and O Ϫ impacting a CEM surface.…”
Section: Resultssupporting
confidence: 59%
“…There have been many attempts to characterize and predict their detection efficiencies for electrons 1,2 and ions. [2][3][4][5][6][7][8][9] Less well studied, however, is their detection efficiency for low energy neutral species. 10 This appears to be primarily due to the lack of facilities able to produce well-characterized, variable energy beams of neutral atoms or molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The absolute detection efficiency across the mass range of our instrument for the MgO-coated CEM is presently unknown. For the same CEM model but without MgO coating and similar ion energies, Keller and Cooper (1996) found the absolute detection efficiency for oxygen to be about 0.6 for positive ions and 0.7 for negative ions. Heavier atomic ions generally have a lower detection efficiency (Krems et al, 2005), e.g.…”
Section: Charge Balancementioning
confidence: 86%
“…Potential mass steps can be found around m/z 24, m/z 48, m/z 58, m/z 65 and m/z 79. These steps could be caused by CN − Arnold et al (1971Arnold et al ( , 1982 and Kopp (1992). The heavy-ion signature is now clearly modulated by the rocket spin (3.6 Hz) with the maxima being about 0.27 s apart and thus requiring 4.5 modulations of the incident ion flux within a full spectrum.…”
Section: Negative Ionsmentioning
confidence: 99%